Fibrinogen-Thrombin Coated Collagen Sponge (TachoSil®) Usage in Rhinoplasty: Our Experience - Yaseen Albar, Naif; Rida Abuzinadah, Haythem; Johannes Lorenz, Kai (ENT Updates, 2020)
Objective: There are multiple techniques to obtain a reasonable augmentation and filling of the nasal dorsum and ensure a smooth and harmonic nasal dorsum in rhinoplasty. This article will discuss our results of applying fibrinogen and thrombin coated collagen patch named TachoSil® in various rhinoplasties, with or without using an additional bone or cartilage graft. Material and Methods: We retrospectively analyzed the preoperative and six months postoperative clinical data as well as the overall satisfaction of a total of 78 patients who were applied TachoSil® during their rhinoplasties between Jan 2016 and July 2019. Results: Rhinoplasties were all performed with a closed approach. No postoperative bleeding and no allergic reactions to TachoSil® were reported. Two patients presented on the 10th postoperative day with nasal dorsum abscess. 83% of the patients were satisfied, whereas nasal retouching was performed in 17% of patients because of dissatisfaction. Conclusion: In addition to its significant hemostatic role, TachoSil® is considered a safe, effective, and easy method to be applied for graft fixation in Augmentation rhinoplasties, to conceal the nasal dorsum irregularities, to fill and support soft tissue in patients with thin nasal skin.